Long-Chain Saturated Fatty Acids, Palmitic and Stearic Acids, Enhance the Repair of Photosystem II - Jimbo, Haruhiko (Int J Mol Sci, 2020)
Free fatty acids (FFA) generated in cyanobacterial cells can be utilized for the biodiesel that is required for our sustainable future. The combination of FFA and strong light induces severe photoinhibition of photosystem II (PSII), which suppresses the production of FFA in cyanobacterial cells. In the present study, we examined the effects of exogenously added FFA on the photoinhibition of PSII in Synechocystis sp. PCC 6803. The addition of lauric acid (12:0) to cells accelerated the photoinhibition of PSII by inhibiting the repair of PSII and the de novo synthesis of D1. α-Linolenic acid (18:3) affected both the repair of and photodamage to PSII. Surprisingly, palmitic (16:0) and stearic acids (18:0) enhanced the repair of PSII by accelerating the de novo synthesis of D1 with the mitigation of the photoinhibition of PSII. Our results show chemical potential of FFA in the regulation of PSII without genetic manipulation.